Development and exploitation features of methane-coal wells using downhole pumping equipment; MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Kurganova E. V. Elena Vladimirovna (2016, 2016)
Title screen